Feasibility of Inspirational Story Text Enrichment Book with Humanist Values - Tri Nur Aeni; Nas Haryati Setyaningsih; Deby Luriawati Naryatmojo (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Books have an important role in the development of students' knowledge and personality as a learning resource. Non-textbooks, especially personality enrichment books, can support student development. Personality enrichment books, such as inspirational stories, have humanist values that can be an example for students and help shape positive character. Therefore, it is important to analyze the feasibility of personality enrichment books with inspirational stories with humanist values for junior high school students. This research uses content analysis research methods. The results of the comparative analysis of the two books show that of the two enrichment books with inspirational story texts containing humanist values, the most appropriate is the enrichment book entitled Cakrawala Life: A Series of Inspirational Family Stories by Arum Yuliya Lestari. Next is an enrichment book entitled Lentera Bangsa: A Collection of Inspirational Stories by Harits Agung Wicaksono.